Global Labor Market Power - Francesco Amodio; Emanuele Brancati; Peter Brummund; Nicolás de Roux; Michele Di Maio (Institute of Labor Economics (IZA), 2024)
We estimate the labor market power of over 13,000 manufacturing establishments across 82 low and middle-income countries around the world. Within local labor markets, larger and more productive firms have higher wage markdowns and pay lower wages. Labor market power across countries exhibits a mild non-linear relationship with GDP per capita, entirely driven by a strong hump-shaped relationship with the share of self-employed workers. Labor market institutions fully account for the hump shape: in countries with unemployment protection, wage markdowns increase with the share of self-employment while the opposite is true in countries without it. We explain this finding through the lens of a simple oligopsonistic labor market model with frictions. Self-employment prevalence correlates with the elasticity of labor supply to the wage paid, and labor market institutions can change the sign of this relationship.
Keywords: J20; J30; J42; L11; 330; labor market power; self-employment; development; labor market institutions